Childhood and adolescence factors and multiple sclerosis: results from the German National Cohort (NAKO) - Holz, Anja; Obi, Nadia; Ahrens, Wolfgang; Berger, Klaus; Bohn, Barbara; Brenner, Hermann; Fischer, Beate; Fricke, Julia Bettina; Führer, Amand-Gabriel; Gastell, Sylvia; Greiser, Karin Halina; Harth, Volker; et al. (BMC neurology, 2024)
Multiple Sclerosis (MS) represents the most common inflammatory neurological disease causing disability in early adulthood. Childhood and adolescence factors might be of relevance in the development of MS. We aimed to investigate the association between various factors (e.g., prematurity, breastfeeding, daycare attendance, weight history) and MS risk.